Psychometric Evaluation of Newly Developed Self-Assessment of Entrepreneurial Competencies - Benedicta Prihatin Dwi Riyanti; Christiany Suwartono (AIBPM Publisher, 2018)
Entering the ASEAN economic community today, Indonesia activelyencourages the number of entrepreneurs. One of the primary resourcesis from the graduates of the vocational high school. The school needsa strategic way to evaluate the improvement of its entrepreneurship curriculum. Therefore, we designed a self-assessment of entrepreneurial competencies. The authors developed an assessment consists of various soft skill and hard skill competencies. Participants were asked to assess own abilities, according to the statements provided. The participants were 258 graduated vocational students from Yogyakarta and Jakarta. From 137 preliminary items, we took 24 best items. Results showed that three-factor model provided an adequate fit for the data. Business management capabilities, strategic thinking skills in managing the business, and the ability to see the opportunities emerged as first-order factors. The reliability estimation with the internal consistency method involved the Cronbach’s alpha for all subtests showed excellent results. Future studies are still needed to test the predictive power of the test tool to the success of graduateswho becomean entrepreneur.